Staged Reconstruction of a Moore Type 4 Fracture Dislocation, Parts 1 and 2. (August 2021) - Schultz, Blake J.; Lowe, Dylan T.; Pean, Christian A.; Alaia, Michael J.; Egol, Kenneth A.
Abstract : Summary: High-energy tibial plateau fractures are associated with knee fracture dislocations and concomitant ligamentous injury. Both bony and ligamentous injuries can require surgical fixation, often requiring a multidisciplinary team and staged treatment. This article and accompanying video describe the workup and treatment of a Moore type 4 tibial plateau rim compression fracture with posterolateral corner and anterior cruciate ligament rupture that underwent open reduction internal fixation of the tibial plateau with posterolateral corner reconstruction and then staged anterior cruciate ligament reconstruction with quad tendon autograft.